Sistem Pendukung Keputusan Untuk Penentuan Lokasi BTS PT. Smartfren Menggunakan Metode Fuzzy-AHP P - nurbhawa, putu roy; Darma Putra, I Ketut Gede; Gunantara, Nyoman (Majalah Ilmiah Teknologi Elektro; Vol 16 No 3 (2017): (September - December) Majalah Ilmiah Teknologi Elektro, 2017)
One way to increase service coverage of telecom operators such as PT. Smartfren is by adding or building new Base Transceiver Stations (BTS). To determine where to place the new BTS, there are several criteria and sub criteria that must be considered. Incorrect choice of criteria and sub criteria or lack of data can cause the new BTS to be built in a less precise location thus the service coverage will not be optimal. Based on that consideration, a decision-making system application to determine BTS location is created using  Fuzzy  AHP method with VB and MySQL applications. The outcome of this application is a list of area, in several regencies, from the highest to the lowest score of BTS location based on the selected criteria and sub-criteria. It helps the user in knowing the most appropriate location for the placement of PT. Smartfren’s new BTS. [TURNITIN 19%, 22022017]
Keywords: Fuzzy AHP, BTS, Criteria, Sub criteria, Decision Support System